The Development of E-Book Using Flip Pdf Pro Through Missouri Mathematics Project Model to Improve Metacognition Abilities and Mathematical Self-Efficacy of Dharma Pancasila Medan High School Students - Wahyudi, Dichi Akbar; Fauzi, M Amin; Ahyaningsih, Faiz (FKIP Universitas Muhammadiyah Tangerang, 2024)
This research aims to describe: 1) The validity, practicality and effectiveness of e-books using flip pdf pro through the Missouri Mathematics Project (MMP) learning model which was developed to improve metacognition abilities and mathematical self-efficacy of SMA Dharma Pancasila Medan students; 2) Increasing students metacognition abilities with e-books using flip pdf pro through the developed MMP learning model; 3) Increasing students mathematical self-efficacy with e-books using flip pdf pro through the developed MMP learning model. This research is development research using the ADDIE development model with a modification of Tessmer formative evaluation. This development model consists of 5 development stages, namely: Analysis, Design, Development, Implementation, and Evaluation. From the results of trial I and trial II, it was obtained: 1) E-book using flip pdf pro through the MMP learning model which was developed to improve students metacognition abilities and mathematical self-efficacy which was developed and met the criteria of being valid, practical and effective; 2) Increasing metacognition abilities with e-books using flip pdf pro through the MMP learning model that has been developed as seen from the N-gain value in trial I of 0.65, increasing to 0.74 in trial II, meaning it is in the category of